Overexpression of TaPIP1A enhances drought and salt stress tolerance in Arabidopsis: cross-species conservation and molecular dynamics - Han, Jie; Zhang, Wei; Zhi, Liya; Chen, Silong; Zhao, Hui; Zhang, Xinyu; Xue, Liuge; Ji, Jun; Wang, Fengzhi; Li, Junming (Frontiers in Plant Science, 2025)
Understanding the mechanisms underlying plant responses to abiotic stress is crucial for improving crop resilience. This study characterizes the role of TaPIP1A, a member of the plasma membrane intrinsic proteins (PIPs) in wheat, highlighting its critical function in mediating stress responses. We demonstrate that TaPIP1A enhances tolerance to salt and drought stress through specific protein-protein interactions and transcriptional regulation. In TaPIP1A knockout wheat strains, there was a significant decrease in stress tolerance, whereas Arabidopsis plants overexpressing TaPIP1A exhibited marked improvements in survival under similar stress conditions.We also discovered that TaPIP1A interacts with TaPIP2-3 and is regulated by the transcription factor TaWRKY71, which binds to its promoter to activate gene expression. These findings contribute to our understanding of the molecular mechanisms by which PIPs facilitate plant adaptation to environmental stresses, offering new avenues for the development of stress-resistant crop varieties. Our research provides insights into the genetic manipulation of intrinsic membrane proteins to enhance plant stress tolerance, a step forward in agricultural biotechnology.